From kitchen to clinic: Pharmacotherapeutic potential of common spices in Indian cooking in age-related neurological disorders - Norouzkhani, Narges; Karimi, Arian Ghannadi; Badami, Negar; Jalalifar, Erfan; Mahmoudvand, Behnaz; Ansari, Arina; Pakrou Sariyarighan, Neda; Alijanzadeh, Dorsa; Aghakhani, Sara; Shayestehmehr, Reza; Arzaghi, Mohammadreza; Sheikh, Zahra; et al. (Frontiers in Pharmacology, 2022)
Aging is described as an advanced time-related collection of changes that may negatively affects the risk of several diseases or death. Aging is a main factor of several age-related neurological disorders, including neurodegenerative diseases (Alzheimer’s disease, Parkinson's disease, and Dementia), Stroke, neuroinflammation, neurotoxicity, brain tumors, oxidative stress and reactive oxygen species (ROS). Currently available medications for age related neurological disorders may lead to several side effects like headache, diarrhea, nausea, gastrointestinal (GI) upset, dyskinesia and hallucinosis. These days, studies on plant efficacy in traditional medicine are being conducted, due to herbal medicine are affordable, safe, it is culturally acceptable and easily accessible. The Indian traditional medicine system called Ayurveda uses several herbs and medicinal plants to treat various disorders including neurological disorders. This review aims to summarize the data on the neuroprotective potential of the common Indian spices widely use in Ayurveda (Cumin (cumium cyminum), Black Cumin (Nigella sativa), Black pepper (Piper nigrum L.), Curry leaves (Murraya koenigii), Fenugreek (Trigonella foenum-graecum), Fennel (Foeniculum vulgare), Cardamom (Elettaria cardamomum), Cloves (Syzgium aromaticum), Coriander (Coriandrum sativum)) in age related neurological disorders.